2020
DOI: 10.1097/wco.0000000000000856
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pathogenesis of spinal bulbar muscular atrophy (Kennedy's disease) and avenues for treatment

Abstract: Purpose of review:To illustrate the current understanding and avenues for developing treatment in spinal and bulbar muscular atrophy (SBMA), an inherited neuromuscular disorder caused by a CAG trinucleotide repeat expansion in the androgen receptor (AR) gene.Recent findings: Important advances have been made in characterizing the molecular mechanism of the disease including the disruption of protein homeostasis, intracellular trafficking, and signaling pathways. Biomarkers such as MRI quantification of muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 57 publications
1
8
0
1
Order By: Relevance
“…Various studies using animal models have shown that circulating testosterone aggravates the neuromuscular phenotype, and testosterone deprivation is beneficial in SBMA, suggesting testosterone-dependent pathophysiology. 14,15 This view is in line with the fact that the early-stage signs of SBMA, i.e., hand tremors and muscle cramps, emerge as early as postpuberty. However, a few studies reported that female carriers also manifest, albeit mild, clinical symptoms such as weakness, muscle cramps, and hand tremors.…”
supporting
confidence: 64%
“…Various studies using animal models have shown that circulating testosterone aggravates the neuromuscular phenotype, and testosterone deprivation is beneficial in SBMA, suggesting testosterone-dependent pathophysiology. 14,15 This view is in line with the fact that the early-stage signs of SBMA, i.e., hand tremors and muscle cramps, emerge as early as postpuberty. However, a few studies reported that female carriers also manifest, albeit mild, clinical symptoms such as weakness, muscle cramps, and hand tremors.…”
supporting
confidence: 64%
“…In a previous clinical trial involving insulinlike growth factor-1 mimetic, thigh muscle volume was used as a primary endpoint and was suggested as a potential marker for monitoring disease progression. 23,24 Therefore, in the clinical setting, an MRI of the thigh may be used as a predictor of gait capacity in patients with SBMA.…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed that the MRI section of the thigh comprising the gracilis, sartorius, semimembranosus, vastus intermedius, and vastus medialis, as well as the patient's age, provided the most comprehensive and a reasonable explanation for the results of the 6MWT in patients with SBMA (see Table 2). In a previous clinical trial involving insulinlike growth factor‐1 mimetic, thigh muscle volume was used as a primary endpoint and was suggested as a potential marker for monitoring disease progression 23,24 . Therefore, in the clinical setting, an MRI of the thigh may be used as a predictor of gait capacity in patients with SBMA.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying the neurodegenerative gain of function in SBMA are not fully understood [114]. Nuclear accumulation and aggregation of polyQ-ARs may contribute to motor neuron degeneration through a variety of molecular mechanisms involving disruption of multiple processes such as transcriptional regulation, protein homeostasis, intracellular trafficking, mitochondrial function and cellular signalling [115].…”
Section: Spinal Bulbar Muscular Atrophy (Sbma)mentioning
confidence: 99%